Combustion optimization for fuel economy improvement of a dedicated range-extender engine. (August 2021) - Wu, Zhenkuo; Han, Zhiyu; Shi, Yongsheng; Liu, Wei; Zhang, Junwei; Huang, Yongcheng; Meng, Shuo
In this study, the combustion system of a dedicated range-extender engine was optimized based on a production engine for fuel economy improvement with the use of enhanced tumble flow, higher compression ratio, Atkinson cycle and exhaust gas recirculation (EGR). First, the shape of the intake port was optimized to improve in-cylinder tumble and turbulence for combustion enhancement. The computational fluid dynamics (CFD) results showed that compared to the original intake port, the peak tumble ratio during the compression stroke of the new port is improved by 74.0%, and the turbulent kinetic energy at the spark timing is increased by 33.0%, and the results were verified through the flow test bench experiment. The dyno experiment showed that, with the new intake port, the engine brake specific fuel consumption (BSFC) was improved for all test conditions. Then, the late intake valve closing (IVC) and a higher compression ratio were used in combination to adopt the Atkinson cycle. The IVC timing was set to 642° ATDC based on the preset power target. And the compression ratio was set to 12 to balance knock tendency and BSFC improvement. Finally, the cooled EGR was optimized to further suppress the knocking tendency to improve fuel consumption. The results showed that, with the cooling Strategy 2, the attainable maximum EGR ratio at 2400 rpm full load and 70 Nm conditions was increased, the spark timing could be significantly advanced, and the BSFC was improved. The improvement of BSFC is between 6 g/kW·h and 13 g/kW·h for the load range from 40 Nm to the full load. After the optimization, the minimum BSFC of the range-extender engine reaches 233 g/kW·h, while it is around 242 g/kW·h for the base engine. The operation area where fuel consumption is lower than 240 g/kW·h becomes much wider.